Relationship between Student Perceptions and Motivation to Join the Spiritual Islamic Extracurricular Program at SMA Negeri 7 Padang - Ema Yulianti; Tasril Bartin (Universitas Negeri Padang, 2021)
This research was motivated by the low motivation of students in joining the Spiritual Islam curricular program at SMA Negeri 7 Padang which allegedly represented students' perceptions. The objectives of this study were to: 1) describe student perceptions, 2) describe student motivation, 3) see the relationship between student perceptions and motivation to take part in the extracurricular spiritual program of Islam at SMA Negeri 7 Padang. This study has a status, namely the perception of students' perceptions of student motivation. The population of this study were students who participated in the Spiritual Islam curricular program at SMA Negeri 7 Padang. The total population is 90 students. The research sample was 46 students who were taken 50% of the population. The research instrument used to collect data about student perceptions and student motivation was a questionnaire using a Likert scale with 4 alternative answers: always, often, rarely, never. To measure the results of the data performed using descriptive statistics and product moment statistical analysis. The results showed that students had low motivation and perception in participating in the Spiritual Islam curricular program at SMA Negeri 7 Padang, and there was a significant relationship between students' perceptions and motivation to take part in the Rohani Islam extracurricular program at SMA Negeri 7 Padang. This is evidenced by the results of calculations using the product moment statistical analysis which shows that the r count (0.609) is greater than the table both at the 5% confidence level (0.291) and the 1% confidence level (0.376).Keywords: Student Perceptions, Motivation, Extracurricular Activities